Ảnh hưởng tỷ lệ cấu tử tới cấu trúc, tính chất của blend trên cơ sở cao su nitril butadien và cao su clopren. - Liên, Trần Kim; Hải, Lươnng Như; Minh, Đỗ Quang; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2012)
In this paper, nitrile butadiene (NBR)/chloroprene (CR) blends were prepared for improving the mechanical properties, the oil, environmental resistance and the thermal stability. The characterization of the mechanical properties were performed according to the Vietnamese Standards. The thermal stability, the morphology of the materials depending on the blend composition was investigated by the thermal gravimetry analysis (TGA) and scanning electron microscopy (SEM). The results show that blend with the NBR/CR composition 50:50 are partly compatible and a well-dispersed and compact structure are obtained. The mechanical properties, oil and environmental resistance and the thermal stability of the materials were significantly improved.